Rise of the Shadowfire - Yogis, Jaimal (Yogis, Jaimal. City of dragons, 2023)
"Grace and her friends are still recovering from the evil attacks plotted by ancient warlord Daijiang when Nate suddenly reappears and whisks Grace away to the Dragon King's lair. There, she learns that Daijiang is searching for a powerful dragon stone that will help him take over the world -- and that he has enlisted a terrifyingly fierce beast called Shadowfire to capture Grace. Pursued by the Shadowfire, Grace and her friends must get to Paris and stop Daijiang's plan. But their new ally, Dr. Kim, may not be all she appears, and a battle looms that could destroy all of Paris!"--